Relation of frailty to outcomes in percutaneous coronary intervention - Kwok, Chun Shing; Achenbach, Stephan; Curzen, Nick; Fischman, David L.; Savage, Michael; Bagur, Rodrigo; Kontopantelis, Evangelos; Martin, Glen P.; Steg, P. Gabriel; Mamas, Mamas A. (Cardiovascular Revascularization Medicine, 2019)
There is growing awareness that frailty may be an important marker of adverse outcomes in PCI but there is no literature from national cohorts. This study examines a national cohort of patients who underwent percutaneous coronary intervention (PCI) regarding the prevalence of frailty, changes over time, and associated outcomes. The National Inpatients Sample was used to identify adults who underwent PCI procedures between 2004 and 2014. Frailty risk was measured using a validated Hospital Frailty Risk Score (HFRS) using the cutoffs <5, 5–15 and >15 for low, intermediate and high HFRS. From 7,306,007 admissions, a total of 94.58% of admissions were for patients who had a low HFRS(<5), 5.39% had an intermediate HFRS(5–15) and 0.03% had a high HFRS(>15). The prevalence of intermediate or high frailty risk patients has increased over time from 1.9% in 2004 to 11.7% in 2014. The incidence of in-hospital death increased from 1.0% with low HFRS to 13.9% with high HFRS. Mean length of stay also increased from 2.9 days to 17.1 days from low to high HFRS. High frailty risk was independently associated with an OR 9.91 95%CI 7.17–13.71 for in-hospital death, OR 4.99 95%CI 3.82–6.51 for bleeding and OR 3.96 95%CI 3.00–5.23 for vascular injury as compared to patients with low risk of HFRS. While rare in frequency overall, frailty is increasing in prevalence in recent years and intermediate and high HFRS associated with increased odds of mortality compared to low risk of frailty.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Complications; Frailty; Mortality; Percutaneous coronary intervention